HBR guide to getting the right work done. - Yen, Jonathan (Harvard business review guides., 2022)
Is your workload slowing you-and your career-down? Your inbox is overflowing. You're paralyzed because you have too much to do but don't know where to start. Your to-do list never seems to get any shorter. You leave work exhausted but have little to show for it. It's time to learn how to get the right work done. In the HBR Guide to Getting the Right Work Done, you'll discover how to focus your time and energy where they will yield the greatest reward. Not only will you end each day knowing you made progress-your improved productivity will also set you apart from the pack. Whether you're a new professional or an experienced one, this guide will help you: prioritize and stay focused; work less but accomplish more; stop bad habits and develop good ones; break overwhelming projects into manageable pieces; conquer e-mail overload; and write to-do lists that really work.